How Are The Portrays And Perceptions Of Students In Physics Experiment? - Maria Agatha Hertiavi; Saiful Ridlo; Budi Naini Mindyarto; Endang Susilaningsih; Wiyanto Wiyanto; Suharto Linuwih; Sri Wardani (Universitas Negeri Semarang, 2022)
Abstract. Science learning is inseparable from practice activities or experiments. A laboratory is a facility to promote these activities. During distance learning, laboratory activities could be promoted at home. This research aims to portray the students' activities during the laboratory practice and to find out the students’ perceptions about the laboratory practice and take-home laboratory practice. The applied method was a survey followed by 80 physics education students of Universitas Pattimura. This research also interviewed three lecturers of the program. Before distributing the questionnaire, the question items were validated in terms of the content. Then, the researchers also examined the reliability of the questionnaire. The findings showed that students did the laboratory practice as they frequently did. They started by having a pretest and ended with a posttest. They also created temporal reports and practical reports for the following meetings. The students were interested in the practice activities because they believed these activities could make them having various skills. Some students recognized the term, take-home practice, by using any surrounding tools and materials. However, most students still considered that laboratory activities should have been done in the laboratory.